(untitled) (Universidad de San Andres Law Review, 2023)
The objective of this paper is to analyze whether the formal guarantees granted by the Mexican Constitution, in terms of the best interests of the child, also become material guarantees. The Mexican legal system, in the first article of its Constitution, safeguards the recognition and application of human rights and international instruments to which the State is part of, for all its citizens, as well as the guarantees for their protection. That is to say, the international instruments subscribed by Mexico regarding the protection of the fundamental rights of minors. Within this set of international instruments, our country recognizes the International Convention on the Rights of the Child, promulgated on November 20, 1989, in New York, to which Mexico adhered, ratified and put the means for its entry into force the following year (1990). Within this legal framework of constitutional rank, the purpose is to verify the materialization of the protection of the rights of minors in matter of child sexual violence, in view of the figures and statistics that show us if this inalienable right is being protected or not, as stipulated by law. This research does not intend to provide a solution to the problems that can and, in fact, do arise. It is only the verification of a legal-judicial gap in the Mexican legal system, the investigation of its possible causes and the analysis of the answers that have been given over time, with the hope that this reality will end and the lives of children will have hope.